2022
DOI: 10.1002/ccd.30249
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of 48 mm Xience Xpedition everolimus‐eluting stent for the treatment of long coronary lesions

Abstract: Introduction Long drug‐eluting stents may limit the issue of overlapping multiple stents when treating long coronary lesions. Aim The aim of the study was to assess the safety and efficacy of the 48 mm Xience Xpedition everolimus‐eluting stent (48mm‐EES) for the treatment of long coronary lesions, in an all‐comer population. Methods Patients receiving at least one 48mm‐EES were prospectively included from March 2014 to December 2018. The primary endpoint was target lesion failure (TLF), defined as a composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(54 reference statements)
1
9
0
Order By: Relevance
“…All these trials, however, indicated that the implantation of a single stent v multiple stents of equivalent length means induces longer fluoroscopy and procedure time, with more contrast volume and, if the stent cost is the same irrespective of length, greater cost. Gautier et al also observed shorter procedure time and reduced contrast volume in single 48 mm EES patients in this study 3 …”
supporting
confidence: 81%
See 4 more Smart Citations
“…All these trials, however, indicated that the implantation of a single stent v multiple stents of equivalent length means induces longer fluoroscopy and procedure time, with more contrast volume and, if the stent cost is the same irrespective of length, greater cost. Gautier et al also observed shorter procedure time and reduced contrast volume in single 48 mm EES patients in this study 3 …”
supporting
confidence: 81%
“…It is with this backdrop that we read with keen interest the study by Gautier et al in this issue of Catheterization and Cardiovascular Interventions, in which the authors provide results of a consecutive series of 268 patients and 276 lesions receiving a 48 mm long everolimus eluting stent (EES) either alone or in combination with other stents. 3 The excellent 1-year outcome (4.1% clinically driven target lesion revascularization (TLR) and 0.8% stent thrombosis with a nearly complete −96.1%follow-up) is even more remarkable if you consider the high prevalence (34%) after chronic total occlusions (CTO) and of small stents (46.1% smaller than 3.0 mm). Deliverability was also excellent with uneventful aborted attempts occurring in 5.3% of cases, a percentage possibly going to drop even more with the claimed better new iterations of this stent design (Skypoint ® , Abbott Vascular).…”
mentioning
confidence: 99%
See 3 more Smart Citations